2020
DOI: 10.1055/s-0040-1712554
|View full text |Cite
|
Sign up to set email alerts
|

Rise in Cases of Alcohol Withdrawal following Lockdown in Dry District of Wardha

Abstract: On March 11, 2020, the World Health Organization declared the SARS-CoV-2 outbreak to be a pandemic which has sent all countries in a frenzy. We cannot be callous about treatment of non-COVID-19-related patients. The Wardha district of Maharashtra is a declared “dry area” which makes the sale, purchase, and consumption of alcohol illegal. On March 24, 2020, Indians were informed of a 21-day long lockdown which was subsequently extended for another 3 weeks during which all modes of public transportation, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Lockdown and sudden alcohol ban in many countries saw a sudden surge in complicated alcohol withdrawal [ 5 ▪▪ , 9 ]. There were also reports of alcohol withdrawal resulting in cases of suicides during the COVID-19 pandemic from India [ 10 , 11 ], raising potential dilemmas of forced abstinence [ 12 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…Lockdown and sudden alcohol ban in many countries saw a sudden surge in complicated alcohol withdrawal [ 5 ▪▪ , 9 ]. There were also reports of alcohol withdrawal resulting in cases of suicides during the COVID-19 pandemic from India [ 10 , 11 ], raising potential dilemmas of forced abstinence [ 12 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…Daily wage workers must look for jobs because there is so much unemployment as a result of the virus's spread. Many studies were reported on effects of lockdown during Covid-19 pandemic [21][22][23]. Spoorty et al reported about mental health problems faced by healthcare workers due to the COVID-19 Pandemic [24].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical offices supplier may even have issues due the weight they are looking from recent months as indicated by SARS COV 2003 Infection had part of post appalling pressing factor issues among medical care supplier's thus during such pandemic there is raised degrees of anxiety among the clinical staff. Serious pressing factor was noticed everywhere on the world during lockdown much more pressing factor was made by the media all over antagonistic vibes were spreading numerous individuals didn't had (13)(14)(15). As it is an expression together we will win ,we will without a doubt win once we contemplate all elements and manage every one bit by bit .…”
Section: Discussionmentioning
confidence: 99%